A ORGANIZAÇÃO DO ESPAÇO DO MUNICÍPIO DE ARAGUAÍNA (TO): leituras a partir da percepção dos moradores do setor Presidente Lula. - MACÊDO, Valéria Pereira (Universidade Federal do Tocantins, 2024)
The city is a place par excellence of reverberations encouraged by a hierarchical societydivided into classes, which produces and reproduces the dynamism of capitalist needs and desires in the spaces of social relations. This process of propagation of society, under the command of capital, gives rise to the Brazilian social issue permeated by inequalities of different meanings and which resonate in housing problems. In this sense, the present study aims to problematize the organization of space in the municipality of Araguaína (TO) based onthe reading of residents of the Presidente Lula sector, with the research problem being that residents of the Presidente Lula sector perceive their own place of housing as well as the city of Araguaína?, taking as a reference the conditions that parameterize the production of urban space referenced in Henri Lefebvre's propositions about the city and the urban. In this sense, we consider that the unequal distribution of wealth transforms the production of space and materializes spaces of social fragility. It is considered as a working hypothesis that the attractiveness of the city, driven by self-marketing centered on the perspective of a competitivecity, drives extra and intra-urban migration, presenting demographic growth rates above the State of Tocantins and Brazil. The study used the methodology referenced in the descriptive- exploratory perspective of a qualitative approach with the interview technique through participant observation and the use of a semi-structured script, the snowball method, saturation, content analysis and the use of webQDA software for content analysis, as well as the elaborationof propositional action. The finals considerations after carrying out thirty-nine interviews, I reaffirm the theoretical perspective adopted when noting the social inequality that echoes in thedistribution of public investment and the disparity in access to the right to the city, such as thevarious precariousness found in the President Lula sector, mobility deficient urban area, presence of recent migratory flows, precarious access to the sector and infrastructure distinctions between internal spaces, leading the less favored population to occupy public or private areas, without economic interest, to live.